Homology modeling and expression of recombinant NS5-RDRP based on the Indonesian local strain of dengue virus for anti-dengue drug development - Subroto, Toto; Firdaus, Ade Rizqi Ridwan; Kusumawardani, Shinta; Tohari, Taufik Ramdani; Nababan, Theresia Adventina; Pertiwi, Wulan; Fadhlillah, Muhammad; Kusuma, Sri Agung Fitri; Rukayadi, Yaya (HH Publisher, 2024)
This study aims to isolate the RNA-dependent RNA polymerase (RdRp) gene of the dengue virus (DENV) isolates from Indonesia, determine the serotype of the local DENV strain through homology modeling, and express the recombinant RdRp protein in Escherichia coli BL21 (DE3), as the target for anti-dengue drug development. We utilize reverse transcription-polymerase chain reaction (RT-PCR) and nested PCR for serotyping the DENV isolates, obtained from Hasan Sadikin Hospital, Indonesia. Then, followed by the extraction and purification of the RdRp amplicon for gene sequencing. The resulting RdRp gene sequences are translated into amino acid sequences, which are then used for protein modeling and the construction of a recombinant plasmid for RdRp protein expression. As a result, the RdRp gene, which belongs to the non-structural protein 5 (NS5) of DENV, was successfully isolated and sequenced from DENV RNA samples. Based on serotyping results and homology modeling, the serotype of the isolate DENV was identified as serotype-3. The isolated NS5-RdRp gene from the local strain was then inserted into the pET28a(+) plasmid and transformed into E. coli BL21(DE3) as the host cell. Recombinant NS5-RdRp was predominantly found in the insoluble fraction with a molecular weight of 72 kDa. Future studies on the development of an anti-dengue drug model that confirms the inhibition of the binding domain in the recombinant RdRp protein structure will be required to provide more insight and expand the development of a universal anti-dengue strategy in Indonesia.